NAVIGATING THE LANDSCAPE OF ADJUVANTS FOR SUBUNIT VACCINES: RECENT ADVANCES AND FUTURE PERSPECTIVES - OROSCO, FREDMOORE L.; ESPIRITU, LLEWELYN M. (International Journal of Applied Pharmaceutics, 2024)
The development of effective subunit vaccines relies on the incorporation of adjuvants to enhance immune responses and improve vaccine efficacy. This paper provides a comprehensive review of the various adjuvants employed in subunit vaccine development, with an emphasis on liposome-based, carbohydrate-based, polymer-based, and nanoparticle-based adjuvants. Additionally, the general concept of vaccine adjuvants, their classification into different types, and the underlying molecular mechanisms by which they exert their immunostimulatory effects are discussed. The use of adjuvants in subunit vaccine development has revolutionized immunization strategies by enhancing vaccine efficacy and inducing robust immune responses. Further research is needed to understand the safety profiles of adjuvants, elucidate the underlying molecular mechanisms, and optimize the adjuvant formulations. By harnessing the power of adjuvants, we can advance the development of effective subunit vaccines against infectious diseases and malignancies, thereby contributing to global health outcomes.